Disease Modeling Using Embryonic Stem Cells: MeCP2 Regulates Nuclear Size and RNA Synthesis in Neurons123. (20th September 2012) - Yazdani, Morteza; Deogracias, RubÉn; Guy, Jacky; Poot, Raymond A.; Bird, Adrian; Barde, Yves‐Alain
Abstract: Mutations in the gene encoding the methyl‐CpG‐binding protein MECP2 are the major cause of Rett syndrome, an autism spectrum disorder mainly affecting young females. MeCP2 is an abundant chromatin‐associated protein, but how and when its absence begins to alter brain function is still far from clear. Using a stem cell‐based system allowing the synchronous differentiation of neuronal progenitors, we found that in the absence of MeCP2, the size of neuronal nuclei fails to increase at normal rates during differentiation. This is accompanied by a marked decrease in the rate of ribonucleotide incorporation, indicating an early role of MeCP2 in regulating total gene transcription, not restricted to selected mRNAs. We also found that the levels of brain‐derived neurotrophic factor (BDNF) were decreased in mutant neurons, while those of the presynaptic protein synaptophysin increased at similar rates in wild‐type and mutant neurons. By contrast, nuclear size, transcription rates, and BDNF levels remained unchanged in astrocytes lacking MeCP2. Re‐expressing MeCP2 in mutant neurons rescued the nuclear size phenotype as well as BDNF levels. These results reveal a new role of MeCP2 in regulating overall RNA synthesis in neurons during the course of their maturation, in line with recent findings indicating a reduced nucleolar size in neurons of the developing brain of mice lacking Mecp2 . STEM Cells 2012;30:2128–2139